„Ruch to zdrowie”, czyli rzecz o popieraniu rozwoju kultury fizycznej przez władze publiczne - Kuchciak, Anna (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2018)
Article 68 (5) of the Constitution of the Republic of Poland from 1997 obliges the public authorities to support the development of physical culture, particularly amongst a special group of people – children and young persons. This paper discusses the implementation of the imposed tasks referred to above in regard both to the provisions of the constitution as well as to the meaning of the key terms under the law and also to solutions arising from selected statutory regulations and executory provisions related to the constitutional obligations
Keywords: Konstytucja RP; kultura fizyczna; sport; wychowanie fizyczne; rehabilitacja ruchowa